Early Dynamic Risk Stratification with Baseline Troponin Levels and 90-minute ST Segment Resolution to Predict 30 Day Cardiovascular Mortality in STEMI: Analysis from CLARITY TIMI-28 - Sherwood, Matthew W. (2010)
BACKGROUND: Troponin is the preferred biomarker for risk stratification in non-ST-elevation ACS. The incremental prognostic utility of the initial magnitude of troponin elevation and its value in conjunction with ST segment resolution (STRes) in STEMI is less well-defined. METHODS: Troponin T (TnT) was measured in 1250 patients at presentation undergoing fibrinolysis for STEMI in CLARITY-TIMI 28. STRes was measured at 90 minutes. Multivariable logistic regression was used to examine the independent association between TnT levels, STRes, and 30-day cardiovascular (CV) mortality. RESULTS: Patients were classified into undetectable TnT at baseline (n=594), detectable but below the median of 0.12 ng/ml (n=330), and above the median (n=326). Rates of 30-day CV death were 1.5%, 4.5%, and 9.5% respectively (P<0.0001). Compared with those with undetectable levels and adjusting for baseline factors, the odds ratios for 30-day CV death were 4.56 (1.72-12.08, P=0.002) and 5.81 (2.29-14.73, P=0.0002) for those below and above the median, respectively. When combined with STRes, there was a significant gradient of risk, and in a multivariable model both baseline TnT (P=0.004) and STRes (P=0.003) were significant predictors of 30-day CV death. The addition of TnT and STRes to clinical risk factors significantly improved the C-statistic (0.86 to 0.90, P=0.02) and the integrated discriminative improvement 7.1% (P=0.0009). CONCLUSIONS: Baseline TnT and 90-minute STRes are independent predictors of 30-day CV death in patients with STEMI. Use of these two simple, readily available tools can aid clinicians in early risk stratification.